Supplementation of glutamine in a short-term boar semen extender during 17°C holding time enhances post-thaw sperm quality for cryopreservation - Morakot Nuntapaitoon; Padet Tummaruk; Junpen Suwimonteerabutr (Porcine Health Management)
Abstract Background Glutamine is a nonessential amino acid and the most abundant amino acid found in the seminal plasma and sperm-rich fraction of boar semen. Glutamine plays an important role in enhancing glutathione (GSH) synthesis. It acts as an effective antioxidant in semen and provides intracellular defense to sperm against oxidative stress. This study aimed to improve the quality of frozen-thawed boar semen by using glutamine supplementation in a short-term semen extender during the holding time at 17 °C before cryopreservation. Results The results indicate that the total motility, progressive motility, LIN, STR, and WOB were the highest in the 20 mM supplementation group at the 2 h timepoint after thawing. Thus, the optimal concentration for glutamine supplementation in short-term boar semen extender during the holding time at 17 °C was 20 mM. Interestingly, at all of the time points after thawing, 20 mM glutamine supplementation exhibited the highest level of sperm viability and membrane integrity when compared to the CONTROL (0 mM) and other experimental dilution groups. Moreover, the acrosome integrity, mitochondrial activity, and capacitation status (F pattern) were significantly greater in the 20 mM supplementation group than the other groups at the 2 h timepoint after thawing. Conclusion Supplementation of glutamine at a concentration of 20 mM in a short-term semen extender (Bio Pig®) during the 17 °C holding time before cryopreservation, which had a standard freezing extender (9.0% glycerol and 1.9% Equex paste), could enhance the post-thaw sperm motility and quality parameters of cryopreservation.